2020
DOI: 10.1088/1361-6471/ab8915
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of backgrounds from cosmogenic 137 Xe in xenon gas experiments using 3 He neutron capture

Abstract: 136 Xe is used as the target medium for many experiments searching for 0νββ. Despite underground operation, cosmic muons that reach the laboratory can produce spallation neutrons causing activation of detector materials. A potential background that is difficult to veto using muon tagging comes in the form of 137 Xe created by the capture of neutrons on 136 Xe. This isotope decays via beta decay with a half-life of 3.8 minutes and a Q β of ∼4.16 MeV. This work proposes and explores the concept of adding a smal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…While siting of the detector is not yet decided, it is interesting to note that NEXT-1t achieves similar sensitivity in relatively shallow laboratories to that of other detectors at much deeper sites. That being said, the possibility exists to further reduce the cosmogenic contribution by adding a small amount of 3 He to the gas [57]. The addition of 0.1% by mass of this isotope would reduce the number of 137 Xe in the active volume of the detector by an order of magnitude.…”
Section: Jhep08(2021)164 7 Discussion and Conclusionmentioning
confidence: 99%
“…While siting of the detector is not yet decided, it is interesting to note that NEXT-1t achieves similar sensitivity in relatively shallow laboratories to that of other detectors at much deeper sites. That being said, the possibility exists to further reduce the cosmogenic contribution by adding a small amount of 3 He to the gas [57]. The addition of 0.1% by mass of this isotope would reduce the number of 137 Xe in the active volume of the detector by an order of magnitude.…”
Section: Jhep08(2021)164 7 Discussion and Conclusionmentioning
confidence: 99%
“…In KamLAND-ZEN, based on the spallation neutron rate and the 136 Xe capture cross section, the production yield is estimated to be (3.9 ± 2.0) × 10 −3 (ton•day) −1 , consistent with their simulation study using FLUKA [170]. Contribution to background in the NEXT experiment is also being computed; moreover, a method has been proposed to mitigate cosmogenic 137 Xe using 3 He [187]. This study, based on GEANT4 simulations, considers the addition of a small quantity of 3 He to xenon in order to capture thermal neutrons and then decrease the detector activation.…”
Section: Activation Studiesmentioning
confidence: 58%
“…For instance, for LNGS, an activation rate of 0.10 kg −1 y −1 is estimated for operation of pure enriched xenon, with a reduction of a factor 10 with the addition of 0.1% 3 He by mass. It is concluded that, thanks to 136 Xe/ 3 He mixtures, the effect of 137 Xe activation on neutrinoless DBD searches can be made negligible for HPXe detectors at the ton scale and beyond operating at any underground laboratory [187].…”
Section: Activation Studiesmentioning
confidence: 99%
“…Gas composition / atomic mass m: The gas in a high pressure xenon gas neutrinoless double beta decay experiment can be assumed to be predominantly 136 Xe with an atomic mass of 136. Possible addition of minority components to reduce diffusion or absorb neutrons, such as 4 He [42,43,44,45] or 3 He [46] respectively may also be present. Unlike electrons, ions are always thermalized at the drift fields of interest, and so a minority component of a light noble gas will not impact either the instantaneous energy spectrum or bulk mobility of drifting ions, and we can assume m =136 amu for the mass of the buffer gas with a reasonable expectation of accuracy for all these cases.…”
Section: Gas and Ion Parametersmentioning
confidence: 99%